Polycarbonate composition as well as preparation method and application thereof

By premixing Sarin resins A and B with glass fibers, the interfacial bonding between glass fibers and PC resin is improved, and a polycarbonate composition with excellent weld line strength, tensile strength and flame retardant properties is prepared, which solves the problem of insufficient weld line strength of glass fiber reinforced PC materials in complex structures.

CN121673798APending Publication Date: 2026-03-17KINGFA SCI & TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202512046785.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-12-31
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing glass fiber reinforced PC materials have poor weld line strength when injection molding complex structures, and conventional improvement methods can affect flame retardant properties.

Method used

A polycarbonate composition was prepared by premixing Salin resin A and Salin resin B with glass fiber and then using a twin-screw extruder. This improved the interfacial bonding between the glass fiber and the PC resin. Toughening agents and flame retardants were added to enhance the weld line strength and flame retardant properties.

Benefits of technology

It significantly improves the weld line strength, tensile strength and flame retardant properties of polycarbonate compositions, while maintaining the high-temperature stability of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a polycarbonate composition as well as a preparation method and application thereof, and relates to the technical field of plastics. The polycarbonate composition provided by the invention comprises the following components in parts by weight: 44-85 parts of polycarbonate; 11 to 21 parts of surlyn resin A; 4 to 15 parts of surlyn resin B; 8 to 32 parts of glass fiber; 0.9 to 13 parts of a toughening agent; 4-11 parts of a flame retardant; the Surlyn resin A is an ethylene-(methyl) sodium acrylate ionic polymer, and the Surlyn resin B is an ethylene-(methyl) zinc acrylate ionic polymer. The polycarbonate composition provided by the invention has excellent weld line strength, flame retardant property and tensile strength.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of plastics, in particular to a polycarbonate composition and a preparation method and application thereof. BACKGROUND

[0002] Polycarbonate (PC) is a kind of amorphous thermoplastic with very high transparency, and is one of the five engineering plastics. The performance of aromatic PC is the best, and the commonly used PC is bisphenol A type PC, which is also the most widely used PC material. Polycarbonate has unique high light transmittance, high impact resistance, dimensional stability and easy processing, and occupies an extremely important position in the optical field. The light transmittance of optical grade polycarbonate (PC) can reach 89%, the haze is less than 0.3%, and the refractive index is 1.58. The obtained product has excellent optical performance, colorless and transparent appearance, and excellent infrared transmission performance. It has a wide application in the application scenarios such as automobile lamp, automobile glass, electronic and electrical window, etc. which require high heat resistance, high rigidity, and high infrared transmission. In recent years, a new riveting method-laser welding has been tried in these fields.

[0003] At present, glass fiber reinforced PC materials have excellent rigidity and toughness balance performance and dimensional precision, and are widely used in fields such as film and television equipment, sound equipment, automobiles, etc. However, when the glass fiber reinforced PC product is used to injection mold a plastic part with a relatively complex structure, the fusion line near the position is poor, that is, the strength of the fusion line of the material is poor. At present, most of the methods for improving the interface bonding of glass fiber and PC resin parts are through compatibilizers, coupling agents and other methods, but the conventional fusion line strength is still poor, and the introduction of surface modifiers will deteriorate the flame retardant performance to different degrees. SUMMARY

[0004] The present application aims to overcome the shortcomings of the prior art and provides a polycarbonate composition and a preparation method and application thereof. The polycarbonate composition has excellent fusion line strength, flame retardant performance and tensile strength.

[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present application is as follows: In a first aspect, the present application provides a polycarbonate composition, comprising the following components by weight: Polycarbonate 44-85 parts; Sarin resin A 11-21 parts; Sarin resin B 4-15 parts; Glass fiber 8-32 parts; Toughening agent 0.9-13 parts; Flame retardant 4-11 parts; The sarin resin A is an ethylene-(meth)acrylic acid sodium ion polymer, and the sarin resin B is an ethylene-(meth)acrylic acid zinc ion polymer.

[0006] Preferably, the mass ratio of the said first and second polyamide is (0.5-6): 1.

[0007] More preferably, the mass ratio of the said first and second polyamide is (1-5): 1.

[0008] Further preferably, the mass ratio of the said first and second polyamide is (2-4): 1.

[0009] Preferably, the said first polyamide has a melt index of 0.5-12 g / 10 min at 190°C / 2.16 kg test conditions.

[0010] More preferably, the said first polyamide has a melt index of 0.6-3 g / 10 min at 190°C / 2.16 kg test conditions, for example can be any one of 0.6 g / 10 min, 1.3 g / 10 min, 2 g / 10 min, 2.2 g / 10 min, 2.5 g / 10 min, 2.8 g / 10 min, 3 g / 10 min or a range value between any two of them.

[0011] Preferably, the said first polyamide has a mass percentage of 8-20% in the polycarbonate composition.

[0012] Preferably, the said second polyamide has a melt index of 1-8 g / 10 min at 190°C, 2.16 kg test conditions.

[0013] More preferably, the said second polyamide has a melt index of 4-7 g / 10 min at 190°C / 2.16 kg test conditions, for example can be any one of 4.0 g / 10 min, 4.2 g / 10 min, 4.4 g / 10 min, 4.6 g / 10 min, 4.8 g / 10 min, 5.0 g / 10 min, 5.2 g / 10 min, 5.5 g / 10 min, 6 g / 10 min, 6.5 g / 10 min, 7 g / 10 min or a range value between any two of them.

[0014] Preferably, the said second polyamide has a mass percentage of 1-17% in the polycarbonate composition.

[0015] Preferably, the total mass percentage of the said first and second polyamide in the polycarbonate composition is 10-40%.

[0016] Preferably, the said polycarbonate is a bisphenol A polycarbonate.

[0017] Preferably, the melt index of the polycarbonate resin under the test condition of 300℃ / 1.2kg is 5-70 g / 10min, for example, can be any one of 5 g / 10min, 10 g / 10min, 15 g / 10min, 20 g / 10min, 25 g / 10min, 30 g / 10min, 35 g / 10min, 40 g / 10min, 45 g / 10min, 50 g / 10min, 60 g / 10min, 70 g / 10min or a range value between any two of them.

[0018] Preferably, the mass percentage of the polycarbonate in the composition is not less than 35%.

[0019] In the present application, the melt index is measured according to GB / T3682.1-2018.

[0020] Preferably, the average diameter of the glass fiber is 8-15 μm, the initial average length is 2-5 mm, and the content of Na2O is 0.1-2wt%.

[0021] If the content of Na2O in the glass fiber is too high, the strength of the glass fiber will be reduced; if the content of Na2O in the glass fiber is too low, the dimensional stability and heat distortion temperature of the glass fiber at high temperature will decrease. Therefore, by controlling the content of Na2O in the glass fiber within the above range, the thermal stability and mechanical properties of the polycarbonate composition are improved.

[0022] Preferably, the toughening agent includes at least one of an organic silicon-based toughening agent, an MBS-based toughening agent, and a polyethylene acrylate-based toughening agent.

[0023] Preferably, the flame retardant includes at least one of a sulfonate flame retardant and a phosphorus-containing flame retardant.

[0024] More preferably, the sulfonate flame retardant includes at least one of potassium perfluoroalkyl sulfonate, potassium benzene sulfonyl benzene sulfonyl, sodium p-toluene sulfonate, and a phosphorus-containing flame retardant, and is further preferably potassium perfluorobutyl sulfonate.

[0025] More preferably, the phosphorus-containing flame retardant includes at least one of hexaphenoxycyclotriphosphazene, triphenyl phosphate, resorcinol-bis(diphenyl phosphate), bisphenol A-bis(diphenyl phosphate), and resorcinol bis[dio(2,6-dimethylphenyl phosphate)], and is further preferably resorcinol bis[dio(2,6-dimethylphenyl phosphate)].

[0026] Preferably, the polycarbonate composition includes the following components by weight: Polycarbonate 50-70 parts; Sarlink resin A 12-20 parts; Sarlink resin B 5-15 parts; glass fiber 10-25 parts; toughening agent 5-10 parts; flame retardant 5-9 parts.

[0027] Preferably, the polycarbonate composition further comprises 0-8 parts of an auxiliary agent.

[0028] Preferably, the auxiliary agent comprises 0-1 parts of an antioxidant, 0-2.5 parts of a lubricant, 0-2 parts of a flame retardant synergist.

[0029] Preferably, the antioxidant comprises a hindered phenolic antioxidant and / or a phosphite antioxidant.

[0030] Preferably, the hindered phenolic antioxidant comprises at least one of antioxidant 1076, antioxidant 1010, antioxidant 330, antioxidant 2246, and further preferably antioxidant 1076 and antioxidant 1010.

[0031] Preferably, the phosphite antioxidant comprises at least one of antioxidant 168, antioxidant PEP-36, antioxidant 38, antioxidant 126, and further preferably antioxidant 168 and antioxidant PEP-36.

[0032] Preferably, the lubricant comprises at least one of pentaerythritol tetrastearate, polyethylene wax, silicone lubricant.

[0033] Preferably, the flame retardant synergist is polytetrafluoroethylene and / or modified polytetrafluoroethylene.

[0034] Preferably, the glass fiber is pre-mixed with the Sarlink resin A and the Sarlink resin B.

[0035] In a second aspect, the present application further discloses a preparation method of the polycarbonate composition, comprising the following steps: After mixing the components, they are added into a double screw extruder, and after granulation and cooling, the polycarbonate composition is obtained. Preferably, the following preparation method is adopted: (1) the Sarlink resin A and the Sarlink resin B are added into a double screw extruder to be pre-mixed, and a pre-mixed material is obtained; (2) then the polycarbonate, the toughening agent, and the flame retardant are added into the pre-mixed material to be uniformly mixed, and after granulation and cooling, the polycarbonate composition is obtained.

[0036] In the present application, the Sarlink resin A and the Sarlink resin B are pre-mixed with the glass fiber, and the ionic Sarlink resin can interact with the glass fiber surface with high polarity, which can effectively improve the surface polarity of the glass fiber and is beneficial to improve the tensile strength and the welding line strength of the material.

[0037] Preferably, the extrusion temperature of the twin-screw extruder is 210-260℃, and the screw speed is 200-1000 rpm.

[0038] Thirdly, the present invention also discloses the application of a polycarbonate composition in automobiles, smart speakers, cosmetics, toys, and VR / AR smart wearable devices. In particular, the above-mentioned polycarbonate composition can be used to prepare parts with high weld line strength, and is especially suitable for preparing complex structural parts such as smart speakers and smart wearables.

[0039] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention, by introducing sarin resin, effectively improves the surface polarity of glass fibers, thereby enhancing the interfacial bonding between the glass fibers and the polycarbonate resin matrix. This improves the weld line strength of the material without affecting its flame retardant properties. Furthermore, by using two sarin resins with different cationicities to modify the glass fibers, this invention effectively optimizes the interface between the polycarbonate resin, the sarin resin, and the glass fiber component, effectively improving the tensile strength and weld line strength of the material. Therefore, this invention, by using sarin resin A and sarin resin B in combination with glass fibers and polycarbonate, effectively improves the weld line strength, flame retardant properties, and tensile strength of the polycarbonate composition. Detailed Implementation

[0040] To better illustrate the purpose, technical solution, and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments, but the scope of protection and implementation of the present invention are not limited thereto.

[0041] Unless otherwise specified, the materials and reagents used in the following examples are commercially available.

[0042] Examples 1-11 Examples of the polycarbonate composition and its preparation method according to the present invention are shown in Table 1.

[0043] The method for preparing the polycarbonate composition includes the following steps: (1) Sarin resin A and Sarin resin B are added to a twin-screw extruder for premixing with glass fiber to obtain a premix; (2) Then, polycarbonate, toughening agent, flame retardant and premix are added to the twin-screw extruder and mixed evenly. After granulation and cooling, a polycarbonate composition is obtained.

[0044] The temperature of the twin-screw extruder is 210-260℃, and the screw speed is 1000 rpm.

[0045] Comparative Examples 1-7 The only difference between the comparative examples and the embodiments is the type and ratio of components, as shown in Table 2.

[0046] In the components described in each embodiment and comparative example: The polycarbonate 1 is manufactured by Wanhua Chemical, with the grade PC 2100, and has a melt index of 10 g / 10 min under the test conditions of 300℃ / 1.2 kg. The polycarbonate 2 is manufactured by Wanhua Chemical, with the grade PC 2600, and has a melt index of 60 g / 10 min under the test conditions of 300℃ / 1.2 kg.

[0047] The sarin resin A1 is an ethylene-(meth)acrylate sodium ionomer: grade 8660, manufactured by Dow Chemical, with a melt index of 10 g / 10 min. The sarin resin A2 is an ethylene-(meth)acrylate sodium ionomer: grade 1601, manufactured by Dow Chemical, with a melt index of 1.3 g / 10 min; The Salin resin B1 is an ethylene-(meth)acrylate zinc ionomer: grade 1605, manufactured by Dow Chemical, with a melt index of 2.5 g / 10 min. The Salin resin B2 is an ethylene-(meth)acrylate zinc ionomer: grade 1705, manufactured by Dow Chemical, with a melt index of 5.5 g / 10 min.

[0048] The glass fiber 1 has an average diameter of 13 μm, an initial average length of 3.0 mm, a Na2O content of 0.3 wt%, a grade of ECS303W-3-K, and is manufactured by China Jushi Co., Ltd. Glass fiber 2: average diameter of 13 μm, initial average length of 4.5 mm, Na2O content of 1.5 wt%, grade of ECS307NB-4.5-K, manufacturer of Chongqing International Composite Materials Co., Ltd. Glass fiber 3: average diameter 13 μm, initial average length 3 mm, Na2O content 2.0 wt%, grade ECS13-03-510H, manufacturer: China Jushi Co., Ltd. Glass fiber 4: average diameter of 10 μm, initial average length of 3.0 mm, Na2O content of 0.18 wt%, grade TFG-3.0-T436, manufacturer: Taishan Glass Fiber Co., Ltd.

[0049] The toughening agent is an organosilicon toughening agent: manufactured by Kaneka Corporation of Japan, with the brand name MR-01.

[0050] The flame retardant is bisphenol A-bis(diphenyl phosphate): manufactured by Zhejiang Wansheng Co., Ltd., with the brand name WSFR-BDP.

[0051] The flame retardant synergist is coated modified polytetrafluoroethylene: manufactured by Shanghai Luju Polymer Technology Co., Ltd., with the brand name FD3150.

[0052] The antioxidants include hindered phenolic antioxidants and phosphite antioxidants in a mass ratio of 1:1; the hindered phenolic antioxidant is β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate n-octadecyl alcohol ester, antioxidant 1076, commercially available; the phosphite antioxidant is tris(2,4-di-tert-butyl)phosphite phenyl ester, antioxidant 168, commercially available.

[0053] The lubricant is pentaerythritol tetrastearate, which is commercially available.

[0054] Unless otherwise specified, all components and raw materials used in the embodiments and comparative examples of this invention are commercially available, and the same type of components and raw materials are used in each parallel experiment.

[0055] Table 1 Table 2 To verify the performance of the polycarbonate composition described in this invention, the polycarbonate compositions prepared in each example and comparative example were injection molded into specimens for testing the following properties.

[0056] Performance testing methods: 1. Tensile strength and weld line strength: Tested in accordance with ISO 527-2019; the weld line specimens are prepared by injection molding of specimens of the same size using a double-injection tensile specimen mold, with a pre-set molten glue pooling in the middle of the specimen to simulate the state of glue pooling in plastic parts during injection molding.

[0057] 2. Flame retardant performance: Tested according to UL94-2018, and the injection molded part was tested using ISO flame retardant test strips.

[0058] 3. Heat distortion temperature: Tested according to ISO 75-1-2013.

[0059] The performance parameters obtained from the above tests are shown in Table 3.

[0060] Table 3 As can be seen from Examples 1-11, the polycarbonate composition of the present invention has a weld line strength of 53 MPa or more, a tensile strength of 55 MPa or more, a flame retardant rating of V-0, and a heat distortion temperature of 112°C or more, indicating that the polycarbonate composition of the present invention has excellent weld line strength, tensile strength, flame retardant properties, and high temperature resistance.

[0061] A comparison of Examples 7-9 with Example 1 shows that Examples 7-9 use glass fibers of different sizes in combination with Sarin resin and polycarbonate, which enables the composition to have a high strength retention rate and effectively improve the weld line strength and tensile strength of the material.

[0062] Comparing Comparative Examples 1-2 with Example 1, it can be seen that if the amount of either Sarin resin A or Sarin resin B is not within the range defined by the present invention, the weld line strength and weld line retention rate of the material are low.

[0063] Comparing Comparative Examples 3-5 with Example 1, it can be seen that Comparative Example 3 did not include Sarin resin A and Sarin resin B, meaning that Sarin resin was not used for surface treatment of the glass fiber. This failed to effectively improve the interfacial bonding strength between the glass fiber and the polycarbonate resin, resulting in a significant reduction in the weld line strength. Comparative Example 4 and Comparative Example 5 also did not include Sarin resin A and Sarin resin B, both of which affected the weld line strength and flame retardant properties of the materials. This indicates that only by using a compound of Sarin resin A and Sarin resin B can the weld line strength and flame retardant properties of the materials be effectively improved.

[0064] As can be seen from the comparison between Comparative Examples 6-7 and Example 1, if the content of sarin resin A and sarin resin B is too low or too high, it will also have a certain impact on the performance of the material. Therefore, by controlling the content of sarin resin A and sarin resin B within the range defined by the present invention, the polycarbonate composition can simultaneously possess excellent weld line strength, tensile strength, flame retardant properties, and high temperature resistance.

[0065] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A polycarbonate composition characterized in that, The components include the following weight parts: Polycarbonate 44-85 parts; Sarin resin A 11-21 parts; Sarin resin B 4-15 parts; Glass fiber 8-32 parts; Toughening agent 0.9-13 parts; Flame retardant 4-11 parts; The Sarin resin A is an ethylene-(meth)acrylic acid sodium ion polymer, and the Sarin resin B is an ethylene-(meth)acrylic acid zinc ion polymer.

2. The polycarbonate composition of claim 1, wherein, The mass ratio of the Sarin resin A and the Sarin resin B is (0.5-6):1; preferably, the mass ratio of the Sarin resin A and the Sarin resin B is (1-5):

1.

3. The polycarbonate composition of claim 1, wherein, The Sarin resin A has a melt index of 0.5-12 g / 10 min under the test condition of 190℃ / 2.16 kg; And / or, the Sarin resin B has a melt index of 1-8 g / 10 min under the test condition of 190℃ / 2.16 kg.

4. The polycarbonate composition of claim 3, wherein, The Sarin resin A has a melt index of 0.6-3 g / 10 min under the test condition of 190℃ / 2.16 kg; And / or, the Sarin resin B has a melt index of 4-7 g / 10 min under the test condition of 190℃ / 2.16 kg.

5. The polycarbonate composition of claim 1, wherein, The polycarbonate resin has a melt index of 5-70 g / 10 min under the test condition of 300℃ / 1.2 kg.

6. The polycarbonate composition of claim 1, wherein, The glass fiber has an average diameter of 8-15 μm.

7. The polycarbonate composition of claim 1, wherein, The toughening agent includes at least one of a silicone-based toughening agent, an MBS-based toughening agent, and a polyethylene acrylate-based toughening agent; And / or, the flame retardant includes at least one of a sulfonate flame retardant and a phosphorus-containing flame retardant.

8. The polycarbonate composition of claim 1, wherein, The polycarbonate further includes the following weight parts of components: 0-1 part of an antioxidant, 0-2.5 parts of a lubricant, and 0-2 parts of a flame retardant synergist.

9. A process for the preparation of a polycarbonate composition according to any one of claims 1 to 8, characterized in that, The method includes the following steps: After mixing the components, the mixture is added to a twin-screw extruder, granulated, and cooled to obtain a polycarbonate composition.

10. Use of the polycarbonate composition according to any one of claims 1-8 in automobiles, smart speakers, cosmetics, toys, and smart wearable devices.

Citation Information

Patent Citations

  • Flame-retarding PC (polycarbonate) / ABS combination and preparation method thereof

    CN101787196A

  • PC / PMMA material for suitcase shell and preparation method thereof

    CN110041683A

  • Thermoplastic compositions of polycarbonate resin and copolymers of ethylene and acrylic or methacrylic acid

    EP0216267A1

  • Halogen-free flame retardant polyester resin compositions and product by using the same

    KR101711299B1